Knowledge, Attitudes, and Practices of Modern Family Planning Among Women of Reproductive Age in Egbeda Local Government Area, Ibadan, Oyo State" (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: Developing countries face rapid population growth due to high fertility rates and low contraceptive prevalence. Nigeria exemplifies this challenge with a high maternal mortality rate and low contraceptive use. Unintended pregnancies, often resulting from inadequate contraceptive measures, contribute significantly to maternal and child mortality. Family planning is a critical intervention that can prevent these outcomes by enabling individuals and couples to anticipate and achieve their desired number of children, thereby improving maternal and child health. Understanding the knowledge, attitudes, and practices surrounding family planning among women of reproductive age is crucial for developing targeted interventions to enhance contraceptive uptake and overall reproductive health.Objectives: This study aims to assess the knowledge, attitudes, and practices of modern family planning among women of reproductive age in Egbeda Local Government Area, Ibadan, Oyo State.Method of Analysis: A structured questionnaire was administered to 250 women aged 18 and above using simple random sampling. Data were analyzed using SPSS version 21, employing descriptive statistics and chi-square tests for hypothesis testing, with a significance level set at P